2014
DOI: 10.1088/0004-637x/785/1/51
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Friction in Cuspy Galaxies

Abstract: In this paper we treat the problem of the dynamical friction decay of a massive object moving in an elliptical galaxy with a cuspidal inner distribution of the mass density. We present results obtained by both self-consistent, direct summation, N-body simulations, as well as by a new semi-analytical treatment of dynamical friction valid in such cuspy central regions of galaxies. A comparison of these results indicates that the proposed semi-analytical approximation is the only reliable in cuspy galactic centra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 44 publications
0
69
0
Order By: Relevance
“…In our model both bmax and bmin vary along the orbit as a function of the local background and satellite properties. Arca-Sedda & Capuzzo-Dolcetta (2014) state that the local approximation overestimates the effects of dynamical friction in the innermost cuspy regions of galaxies, however in our approach the maximum impact parameter tends to zero at small radii for cuspy distributions, reducing the range at which the local approximation acts over. For distributions with γ > 1 this local scale length is smaller than the distance semi-analytic Gadget Figure 21.…”
Section: Comparison With Arca-sedda and Capuzzo-dolcetta (2014)mentioning
confidence: 55%
See 1 more Smart Citation
“…In our model both bmax and bmin vary along the orbit as a function of the local background and satellite properties. Arca-Sedda & Capuzzo-Dolcetta (2014) state that the local approximation overestimates the effects of dynamical friction in the innermost cuspy regions of galaxies, however in our approach the maximum impact parameter tends to zero at small radii for cuspy distributions, reducing the range at which the local approximation acts over. For distributions with γ > 1 this local scale length is smaller than the distance semi-analytic Gadget Figure 21.…”
Section: Comparison With Arca-sedda and Capuzzo-dolcetta (2014)mentioning
confidence: 55%
“…This frictional force is likely responsible for galactic mergers (Gan et al 2010;Peirani et al 2010), the accretion of satellites and globular clusters onto the Galaxy (Gan et al 2010;Arca-Sedda & Capuzzo-Dolcetta 2014), and even (in part) the coalescence of supermassive black holes (Begelman et al 1980). Numerical simulations using both direct summation codes and collisionless codes have shown that Chandrasekhar's formula (equation 1) works remarkably well, despite the fact that it likely misses important physics like res-E-mail: j.petts@surrey.ac.uk onant interactions between the infalling body and the background (Tremaine & Weinberg 1984;Inoue 2009;Weinberg 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the NSC forms by accreting gas-free GCs that spiral into the galaxy's centre due to dynamical friction (e.g. Tremaine et al 1975;Arca-Sedda & Capuzzo-Dolcetta 2014). Consequently, the formed NSC should reflect the properties of the accreted GCs that are typically more metal-poor than their hosts (e.g.…”
Section: Insights On Nuclear Star Cluster Formationmentioning
confidence: 99%
“…Different mechanisms for funnelling gas to the centre have been studied, such as magnetorotational instability, gas cloud mergers or instabilities from bar structures (Milosavljević 2004;Bekki 2007;Schinnerer et al 2008). On the other hand, NSC formation might happen through gas-free accretion of GCs that have formed at larger galactic radii and migrate inwards due to dynamical friction (Tremaine et al 1975;Capuzzo-Dolcetta 1993;Capuzzo-Dolcetta & Miocchi 2008;Agarwal & Milosavljević 2011;Arca-Sedda & Capuzzo-Dolcetta 2014). Also, the formation of nuclear stellar disks via this channel has been explored (Portaluri et al 2013).…”
Section: Introductionmentioning
confidence: 99%